PERAN EKSTRAKURIKULER DAKWAH DALAM MENINGKATKAN PUBLIC SPEAKING SANTRI PONPES DARUSSALAM PUTRI UTARA BLOKAGUNG BANYUWANGI - Maskur Maskur; Indah Pronika (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2022)
This research focuses on the problem: the role of extracurricular da'wah in improving the public speaking of the students of the Darussalam Putri Utara Islamic boarding school, which is then translated into several problem formulations as follows: (1) how is the role of extracurricular da'wah in improving the public speaking of the students of the Darussalam Putri Utara Islamic Boarding School Blokagung Banyuwangi (2) what are the obstacles in improving the public speaking of the students of Pondok Pesantren Darussalam Putri Utara Blokagung Banyuwangi. This research uses a qualitative descriptive research type, which was held at the Pondok Pesantren Darussalam Putri Utara Blokagung Banyuwangi. The research data were obtained through observation, interviews, and documentation. The results of this study indicate that the role of extracurricular da'wah in improving the public speaking of the students of the Darussalam Putri Utara Islamic boarding school is very instrumental in increasing self-confidence, speaking fluently in public, relieving nervousness, being able to convey messages well, can cause positive feedback to the audience. , make the audience happy to listen to the communicator, and promote critical thinking. The obstacles in public speaking are semantic disorders in language, individual problems, physical disorders, status disorders, and frame of mind disorders.